Factors Affecting Non-relapse Drug Addiction of Rehabilitative Patients in Mueang District, Yala Province - Jehsmajeh, sakeeyah; Thammakun, Theerawut; Chankong, Warangkana (Al-HIKMAH Journal, 2021)
This cross-sectional research aimed to study factors affecting non-relapse drug addiction of rehabilitative patients in Mueang district, Yala province. The study involved 125 patients randomly selected from all 250 drug rehab patients in Mueang Yala district, based on the sample size calculated using the finite population formula. Data were collected using a questionnaire with the reliability values for drug knowledge of 0.74, attitudes of 0.78, internal locus of control of 0.82, future-oriented and self-control of 0.99 and social support factor of 0.87. Statistics for data analyses were frequency, percentage, mean, standard deviation, and logistic regression. The results demonstrated that, among all participants: their drug knowledge and non-drug use attitudes level was high; and moderate for internal locus of control, future-oriented and self-control, and social support; and the factors affecting non-relapse drug addiction of rehabilitative patients in the district were occupation, income, non-drug use period, narcotic drug knowledge, and internal locus of control.